PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PERTAMINA EP ASET 1 LIRIK - Maralis, Reni (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research was conducted at Pertamina Ep Aset 1 Lirik. The purpose of this study was to determine the effect of leadership and organizational commitment on employee performance on pertamina Ep Aset 1 Lirik. The study was conducted with quantitative methods, namely research that describes the influence of leadership and organizational commitment on employee performance on pertamina Ep Aset 1 Lirik. From the results of the study with the regression equation Y = 1.992 + 0.304 X1 + 0.571 X2. a = constant of 1,992 and if the independent variable is zero (0) then the performance of employees is equal to 1,992 meaning that employee performance is 1,992 if X1 (leadership) and X2 (organizational commitment) = 0. b1 = leadership regression coefficient of 0,304 indicates that each increase leadership of one unit and variable organizational commitment remains, an increase in employee performance of 0.304. b2 = regression coefficient organizational commitment of 0.571 shows that every increase in organizational commitment of one unit and fixed leadership variables, then employee performance is 0.571. Correlation coefficient is known that R is 0.830 means that it has a very strong and direct relationship. and the multiple determination coefficient (R2) is 0.689. this shows that (X1) leadership and (X2) organizational commitment together can have an influence on variable (Y) employee performance by 68.9%. And the remaining 31.1% is influenced by other variables. Hypothesis testing at a significant level = 5% where F count is 50,956, while F tables can be obtained using table F with free degrees (df) residuals (46) as df denominator and df Regresion (treatment) that is 2 as df numerator with significant level of 0.05, so that F table 3.20 is obtained because F count (50,956)> F table (3,20) then Ho is rejected and Ha is accepted. This means that leadership variables and organizational commitment simultaneously have a significant influence on employee performance at the Ep Aset 1 Lirik. And a Partial Test is carried out where see t count the leadership variable is 2.036 in table t obtained 2.012. because t count (2,036)> from t table (2,012) then Ho is accepted and Ha is rejected, which means that leadership has a significant influence on employee performance. t count for the variable organizational commitment is 4.278, in table t with db 46 and a significant level of 0.025 is obtained 2.012. because t count (4,278)> from t table (2,012) then Ho is accepted and Ha is rejected, which means that organizational commitment has a significant influence on employee performance. From the results of the calculation, the validity test shows that r count> r table at a significance value of 5%. Therefore, it can be concluded that all data in this study are valid. And the reliability test obtained an Alpha value of 0, 837, while the r value of 0.05 with the amount of data (n) = 49 was obtained at 0.275 because the value was> 0.275, it was concluded that the results of the study were reliable